Biology of Anagrus incarnatosimilis and Anagrus breviphragma (Hymenoptera: Mymaridae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Anagrus incarnatosimilis Soyka and A. breviphragma Soyka were obtained from overwintering eggs of Cicadella viridis (L.) (Homoptera: Cicadellidae).When reared on Dicranotropis hamata (Boheman) or Muellerianella fairmairei (Perris) (Homoptera: Delphacidae) both Anagrus species are solitary parasitoids; both species are facultatively gregarious parasitoids in C. viridis eggs, yielding up to eight progeny per host.One insemination sufficed to produce fertilized eggs throughout the life of the female, although occasionally a second copulation was observed in A. breviphragma.Inseminated A. breviphragma females produced 45.2 ± 22.7 progeny (n = 24); virgin females, only 33.3 ± 21.6 males (n = 24). Mated and virgin A. breviphragma females laid 64 and 62% of their egg complement, respectively, between 6-12 h after their emergence.Eclosion began 3 days after oviposition and lasted approximately one day at 20 °C. Both species had 2 larval instars. First-instar larvae were immobile and absorbed their food. Second instar larvae were very active appearing 5 days after oviposition. This instar doubled in body size. No difference was detected between mandible sizes of early second instar and the mature larva.The prepupal and pupal stages lasted 1 and 6- 7 days respectively in both species.Changes in coloration permited estimation of pupal age. Adult emergence began after 21 days, but most adults emerged 23-24 days after oviposition.
Keywords: Mymaridae; reproductive potential; oviposition; development; egg parasitoids